Health and Labor Force Participation of the Elderly in Taiwan - Cem Mete; T. Paul Schultz (Yale University, Economic Growth Center, 2002)
Estimates are reported of the consequences of health on participation in the labor force of elderly men and women in Taiwan from 1989 to 1996. Three survey indicators of individual health are examined, and two are estimated by instrumental variables (IV), using as instruments parent longevity, birthplace, and childhood conditions. IV estimates of health's effect on participation are in most cases significant and always positive, and about twice the magnitude of the ordinary least squares estimates, and the hypothesis that health is exogenous and measured without error is rejected. Implementation in 1995 of a National Health Insurance (NHI) shifted to the state the growing cost of elderly health care, and reduced the incentive for elderly to work to receive employer-provided health insurance. But this change in health care financing does not appear to have contributed to a reduction in elderly participation rates in 1996.
Keywords: J22; J26; I10; I18; 330; Labor Force Participation; Elderly; Health Status; National Health Insurance; Taiwan; Erwerbstätigkeit; Gesundheit; Ältere Arbeitskräfte; Gesetzliche Krankenversicherung; Taiwan